Monitoring fine and ultrafine particles in the atmosphere of a Southeast Chinese city - Jian, Le; Zhu, Y.; Zhao, Yun (Royal Society of Chemistry, 2011)
There have been few studies on submicron particles in the atmosphere reported from developing countries. With rapid economic development, the size of the road vehicle fleet has increased dramatically in China. The increase in vehicle emissions has raised concerns about air quality, especially in the urban areas of this developing country. A model study was conducted in Hangzhou, a city in Southeast China, with the aim of characterizing the emission patterns of submicron particles ≤1.0 micron from on-road vehicles and the impact of vehicle density and speed on the concentrations of submicron particles in the atmosphere. Results showed that the average ultrafine particle (UFP) number concentration was 45805 particles cm−3 and the average mass concentration of particulate matter 1.0 (PM1.0) was 217 μg m−3 during the survey period. Autoregressive Integrated Moving Average modelling results indicated that an increase of vehicle density and driving speed were positively correlated with the increase of UFP and PM1.0 concentrations (p < 0.05) in the atmosphere. Results from this study suggest that vehicle density and driving speed are significant predictors of submicron particle emissions. This study provides first hand information for future investigations on the submicron particle emissions in Hangzhou, a city with rapidly increasing vehicle numbers and for further investigations into a possible causal relationship between submicron particles and health effects on local residents.